The conditional effects of the refugee crisis on immigration attitudes and nationalism. (June 2021) - van der Brug, Wouter; Harteveld, Eelco
What was the impact of the 2014–2016 refugee crisis on immigration attitudes and national identification in Europe? Several studies show that radical right parties benefitted electorally from the refugee crisis, but research also shows that anti-immigration attitudes did not increase. We hypothesize that the refugee crisis affected right-wing citizens differently than left-wing citizens. We test this hypothesis by combining individual level survey data (from five Eurobarometer waves in the 2014–2016 period) with country level statistics on the asylum applications in 28 EU member states. In Western Europe, we find that increases in the number of asylum applications lead to a polarization of attitudes towards immigrants between left- and right-leaning citizens. In the Southern European 'arrival countries' and in Central-Eastern Europe we find no significant effects. Nationalistic attitudes are also not affected significantly.